Role of Ursodeoxycholic Acid in Treating and Preventing Idiosyncratic Drug-Induced Liver Injury. A Systematic Review - Robles-Díaz, Mercedes; Nezic, Lana; Vujic-Aleksic, Vesna; Björnsson, Einar S. (Frontiers in Pharmacology, 2021)
Introduction: Treatment is generally not available for drug-induced liver injury (DILI) patients except in some specific circumstances. The management of DILI is based on the withdrawal of the responsible drug and monitoring the patients and only a few patients need to be referred to a transplant center. Some studies on the role of ursodeoxycholic acid (UDCA) in DILI have been published. The aim of this study was to perform a systematic review of the role of UDCA in the treatment and prevention of DILI. Methods: A search was undertaken in PubMed, with the key words ursodeoxycholic acid, drug-induced liver injury and hepatotoxicity following the PRISMA guidelines. Results: A total of 33 publications were identified: 25 case reports and 8 case series. In 18 of the 25 cases reports (22 patients), authors reported improvement of liver injury associated with UDCA therapy whereas 7 case reports did not show clinical or biochemical improvement after UDCA treatment. There were 4 studies evaluating the role of UDCA in the treatment of DILI, three prospective (one being a clinical trial) and one retrospective studies. Three studies observed liver profile improvements associated with UDCA. In addition, four studies evaluated UDCA in the prevention of DILI: one pilot study, two randomized clinical trials (RCT) and one retrospective study. Three of these studies observed a lower percentage of patients with an increase in transaminases in the groups that used UDCA for DILI prevention Conclusions: According to available data UDCA seems to have some benefits in the treatment and prevention of DILI. However, the design of the published studies does not allow a firm conclusion to be drawn on the efficacy of UDCA in DILI. A well designed RCT to evaluate the role of UDCA in DILI is needed.